Exploring the potential of dietary factors and plant extracts as chemopreventive agents in oral squamous cell carcinoma treatment - Kumar, Madhav; Jha, Abhimanyu Kumar (Frontiers in Oral Health, 2023)
Oral cancer, particularly Oral Squamous Cell Carcinoma (OSCC), is a prevalent malignancy having significant fatality rate worldwide. Despite advancements in conventional treatment modalities, the overall survival rate for OSCC remains low. Therefore, there is a critical need to explore alternative therapeutic approaches that can improve patient outcomes. This review focuses on the potential of natural compoundsDietary factors and Pplant extracts as chemopreventive agents in treating oral cancer. These compounds possess diverse biological functions encompass a range of attributes, such as antioxidative, anti-inflammatory and anticancer capabilities. By targeting multiple cellular pathways involved in carcinogenesis, they possess the capacity to hinder tumour growth and development, promote programmed cell death and impede the progression of oral cancer. Signalling pathways targeted by natural compounds which have been included in this review include Akt/mTOR/NF-κB signalling, Hippo-tafazzin (TAZ) signalling pathway, Notch signalling pathway and Mmitochondrial pathway,. Sonic Hedgehog Pathway.